Determinant Analysis of Factors Affecting the Incidence of Vaginal Discharge among Adolescent Girls - Triana Indrayani; Mujellalah Mujellalah; Jenny Anna Siauta (Global Medical & Health Communication (GMHC), 2026)
Vaginal discharge is a common reproductive health problem among adolescent girls and is often associated with inadequate knowledge and poor hygiene practices. In Indonesia, its high prevalence can negatively affect adolescents' health and quality of life. This study aimed to identify the most dominant factors influencing the incidence of vaginal discharge among adolescent girls at a junior high school in Central Jakarta. A cross-sectional design was applied from June to July 2024, involving 144 ninth-grade female students selected through random sampling. Data were collected using structured questionnaires and analyzed using univariate, bivariate (chi-square), and multivariate logistic regression analyses. The results showed significant associations between knowledge, personal hygiene behavior, panty liner use, physical activity, perineal hygiene, anemia, and the incidence of vaginal discharge. Multivariate analysis revealed that physical activity was the most influential factor (OR=14.949). This finding suggests that inadequate or inappropriate physical activity may disrupt hormonal balance, particularly estrogen regulation, which plays a crucial role in maintaining vaginal glycogen levels and acidity. Such disruption can alter the vaginal microenvironment, reduce the dominance of protective Lactobacillus bacteria, and increase susceptibility to abnormal vaginal discharge. In conclusion, physical activity emerged as the most dominant determinant of vaginal discharge among adolescent girls, alongside other behavioral and physiological factors. These findings highlight the importance of promoting balanced physical activity and comprehensive reproductive health education as preventive strategies for vaginal discharge in adolescents.